Big data using smart big data, analytics and metrics to make better decisions and improve performance - Marr, Bernard (Wiley, 2015)
"There is so much buzz around big data. We all need to know what it is and how it works - that much is obvious. But is a basic understanding of the theory enough to hold your own in strategy meetings? Probably. But what will set you apart from the rest is actually knowing how to USE big data to get solid, real-world business results - and putting that in place to improve performance. Big Data will give you a clear understanding, blueprint, and step-by-step approach to building your own big data strategy. This is a well-needed practical introduction to actually putting the topic into practice. Illustrated with numerous real-world examples from a cross section of companies and organisations, Big Data will take you through the five steps of the SMART model: Start with Strategy, Measure Metrics and Data, Apply Analytics, Report Results, Transform."--
Includes index. - Includes bibliographical references and index. - Print version record and CIP data provided by publisher
Keywords: Information technology -- Management; Big data; Management -- Statistical methods; Decision making -- Statistical methods; Technologie de l'information; Gestion; Données volumineuses; Gestion; Méthodes statistiques; Prise de décision; Méthodes statistiques; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Decision making; Statistical methods; Information technology; Management; Management; Statistical methods; Business & Management; Management & management techniques; Knowledge management; Business and Management